Relationship between mental health and spiritual wellbeing among hemodialysis patients: a correlation study - Martínez, Beatriz Bertolaccini; Custódio, Rodrigo Pereira (São Paulo Medical Journal, 2014)
CONTEXT AND OBJECTIVE: The stress of living with a terminal disease has a negative impact on the mental health of hemodialysis (HD) patients. Spirituality is a potential coping mechanism for stressful experiences. Studies on the relationship between spirituality and mental health among HD patients are scarce. The purpose of this study was to evaluate the relationship between mental health and spiritual well-being among HD patients. DESIGN AND SETTING: Cross-sectional observational study on hemodialysis patients at a single center in Brazil, between January and December 2011. METHODS: Mental health was assessed using the General Health Questionnaire and spiritual wellbeing was assessed using the Spiritual Wellbeing Scale; 150 HD patients participated in the study. RESULTS: A significant correlation was found between mental health and spiritual wellbeing (P = 0.001). Spiritual wellbeing was the strongest predictor of mental health, psychological distress, sleep disturbance and psychosomatic complaints. CONCLUSION: Poor mental health was associated with lower spiritual wellbeing. This has important implications for delivery of palliative care to HD patients.